2017
DOI: 10.1044/2016_jslhr-s-15-0291
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Contrastive Stress on Vowel Acoustics and Intelligibility in Dysarthria

Abstract: Contrastive stress affected vowel formants for both groups. Perceptual results suggest that some speakers with dysarthria may benefit from a contrastive stress strategy to improve vowel intelligibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Clinical Implications: The literature has already established clear links between vowel production and intelligibility in patients with only mild dysarthric symptoms (Connaghan & Patel, 2017;Kim et al, 2011;Skodda et al, 2011). Our research adds to the growing body of literature showing that a reduced vowel space as well as an overlap of vowel categories can already be considered as one part of the symptom complex of a beginning Parkinson's disease.…”
Section: General Assessment Of the Participantsmentioning
confidence: 57%
“…Clinical Implications: The literature has already established clear links between vowel production and intelligibility in patients with only mild dysarthric symptoms (Connaghan & Patel, 2017;Kim et al, 2011;Skodda et al, 2011). Our research adds to the growing body of literature showing that a reduced vowel space as well as an overlap of vowel categories can already be considered as one part of the symptom complex of a beginning Parkinson's disease.…”
Section: General Assessment Of the Participantsmentioning
confidence: 57%
“…Increased acoustic vowel contrast is associated with improved speech intelligibility (e.g., Connaghan & Patel, 2017;Kim, Hasegawa-Johnson, & Perlman, 2011;Turner et al, 1995); hence, increased acoustic vowel contrast is highly desirable for these talkers.…”
Section: Discussionmentioning
confidence: 99%
“…To determine if MDC and MCID differed across severities, it was necessary to classify participants into severity groups. Although several studies have reported grouping participants by severity of intelligibility deficits (Blaney & Hewlett, 2007;Connaghan & Patel, 2017; dos Santos Barreto & Zazo Ortiz, 2016;Doyle et al, 1997;Hustad, 2006;2007;2008;Kent et al, 1989;Kim, Martin, Hasegawa-Johnson, & Perlman, 2010), these authors used widely varying categories, and these categories were based on differing criteria (e.g., sentence intelligibility on the SIT vs. scaled intelligibility of a conversation sample or reading passage) and different populations (e.g., cerebral palsy, Parkinson's disease). This motivated our use of two different stratification schemes for examining the effect of baseline intelligibility on the MDC: (a) a clinical weighting of dysarthria severity based on clinical acumen of SIT scores and (b) an unbiased stratification of scores based on quantiles of the SIT intelligibility scores, which is presumably assumption free (see Figure 1).…”
Section: Dysarthria Severity Classificationmentioning
confidence: 99%